Bioresorbable Scaffolds: Current Evidence and Ongoing Clinical Trials - Bourantas, Christos V. (Current Science Inc., 2012)
Bioresorbable scaffolds (BRS) represent a novel approach in coronary stent technology. In contrast to the metallic stents, they provide transient scaffolding, thereby safeguarding early vessel patency and acute gain. Subsequently a process of “decomposition” occurs, that results in the complete absorption of the scaffold. This reduces the risk of late complications, allowing the vessel to maintain its integrity and physiological function. This unique ability has attracted interest and nowadays several BRS are available. The aim of this review article is to describe the advances in the field, present the evidence from the preclinical and clinical evaluation of these devices, and provide an overview of the ongoing clinical trials that were designed to examine the effectiveness of BRS in the clinical setting.